First Calculations of Starspot Spectra Based on 3D Radiative Magnetohydrodynamics Simulations - H. N. Smitha; Alexander I. Shapiro; Veronika Witzke; Nadiia M. Kostogryz; Yvonne C. Unruh; Tanayveer S. Bhatia; Robert Cameron; Sara Seager; Sami K. Solanki (The Astrophysical Journal Letters)
Accurate calculations of starspot spectra are essential for multiple applications in astronomy. The current standard is to represent starspot spectra by spectra of stars that are cooler than the quiet star regions. This implies approximating a starspot as a nonmagnetic 1D structure in radiative–convective equilibrium, parametrizing convective energy transport by mixing-length theory. It is the inhibition of convection by the starspot magnetic field that is emulated by using a lower spot temperature relative to the quiet stellar regions. Here, we take a different approach, avoiding the approximate treatment of convection and instead self-consistently accounting for the interaction between matter, radiation, and the magnetic field. We simulate spots on G2V, K0V, and M0V stars with the 3D radiative magnetohydrodynamics code MURaM and calculate spectra ( R  ≈ 500 from 250 to 6000 nm) using ray-by-ray radiative transfer with the MPS-ATLAS code. We find that the 1D models fail to return accurate umbral and penumbral spectra on K0V and M0V stars, where convective and radiative transfer of energy is simultaneously important over a broad range of atmospheric heights, rendering mixing-length theory inaccurate. However, 1D models work well for G2V stars, where both radiation and convection significantly contribute to energy transfer only in a narrow region near the stellar surface. Quantitatively, the 1D approximation leads to errors longward of 500 nm of about 50% for both umbral and penumbral flux contrast relative to quiet star regions on M0V stars and less than 2% (for umbrae) and 10% (for penumbrae) for G2V stars.